Bilateral sphenopalatine ganglion block reduces blood pressure in never treated patients with essential hypertension. A randomized controlled single-blinded study. (1st January 2018) - Triantafyllidi, Helen; Arvaniti, Chrysa; Schoinas, Antonios; Benas, Dimitris; Vlachos, Stefanos; Palaiodimos, Leonidas; Pavlidis, George; Ikonomidis, Ignatios; Batistaki, Chrysanthi; Voumvourakis, Costas; Lekakis, John
Abstract: Background: Sympathetic fibers connect sphenopalatine ganglion (SPG) with the central nervous system. We aimed to study the effect of SPG block in blood pressure (BP) in never treated patients with stage I-II essential hypertension. Methods: We performed bilateral SPG block with lidocaine 2% in 33 hypertensive patients (mean age 48 ± 12 years, 24 men) and a sham operation with water for injection in 11 patients who served as the control group (mean age 51 ± 12 years, 8 men). All patients have been subjected to 24 h ambulatory blood pressure monitoring prior and a month after the SBG block in order to estimate any differences in blood pressure parameters. We defined as responders to SBG block those patients with a 24 h SBP decrease ≥ 5 mm Hg. Results: We found that 24 h and daytime DBP ( p  = 0.02) as well as daytime DBP load ( p  = 0.03) were decreased in the study group a month after SPG block. In addition, a significant response was noted in 12/33 responders (36%) regarding: a. SBP and DBP during overall 24 h and daytime ( p  < 0.001) and night-time periods, b. pre-awake and early morning SBP and c. SBP (daytime and night-time) and DBP (daytime) load. No differences regarding BP were found in the sham operation group. Conclusions: SPG block is a promising, minimally invasive option of BP decrease in hypertensives, probably through SNS modulation. Additionally, due to its anesthetic effect, SPG block might act as a method of selection for those hypertensive patients with an activated SNS before any other invasive antihypertensive procedure.